Fractional Recrystallization Behavior of Impurity-Doped Commercially Pure Aluminum - Mohammad Salim Kaiser (University of Muhammadiyah Malang, 2020)
This manuscript reports the effects of trace impurities on the fractional recrystallization behavior of commercially pure aluminum. To allow the recrystallization cold rolled by 75% alloy samples are annealed isothermally at 700ºK for different time up to 60 minutes. Recrystallization kinetics is evaluated from the micro hardness variation of the different annealed samples. The JMAK type analysis is also used to study the recrystallization behavior as well as to observe the correlation with the experimental results. The behavior of the fraction recrystallization between two methods the trace impurities added alloys is evidence for the higher variation as to form GP zones and metastable phases during annealing. Higher addition shows the more variation as the formation of higher fraction phases. The microstructural study reveals that annealing at 700ºK for 30 minutes the alloys attain almost fully re-crystallized state.